Classroom practices of English language teachers at the primary stage in the Southern Mazar Directorate, and their impact on gender and experience - Al - Eidi, Rabaa Mohammed Sulaiman (Journal of Educational and Psychological Sciences, 2017)
The study aims to identify the level of classroom teaching practices of the English teachers of the primary stage in the Southern Mazar Directorate in Karak governorate and their impact on the gender variables and the teaching experience (short, medium and long). The study sample consisted of (43) teachers and teachers of the English language who studied the basic stage in the Directorate of Southern Mazar in Karak governorate were randomly selected cluster. To measure the classroom teaching practices of the sample members, a five-step questionnaire was used (19) after verifying its validity and stability. In order to answer the study questions, the arithmetical averages, the standard deviations of the study sample as well as the T-test and the ANOVA were calculated. The results of the study showed that the level of the teaching practices of the teachers in the English language came at the macro level, The results of the analysis of the binary variance showed that there were statistically significant differences due to the sex variable (male, female) and for the females, and there were no statistically significant differences due to the variable of teaching experience (short, medium or long).
Keywords: classroom teaching practices; English language teacher; teaching experience